1967
DOI: 10.3171/jns.1967.27.3.0274
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Acrylic Plastic for Vertebral Replacement or Fixation in Metastatic Disease of the Spine

Abstract: RYLIC plastics have been used extensively in the repair of skull defects 10.12 and have been tried not too successfully as replacement therapy for worn-out intervertebral discs, 2,'~ for internal fixation in fractures, and in arthritic spines?-4,7-9,n Dott of Edinburgh 3 mentioned his use of acrylic plastic in atlanto-axial subluxation from rheumatoid arthritis, and his associate Harris ~ has written of further uses including the fixation of fractures of the cervical spine. Clinical and aninml work has shown t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
4

Year Published

1976
1976
2011
2011

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(26 citation statements)
references
References 5 publications
0
22
0
4
Order By: Relevance
“…Defect-restoration with bone cement or a cage is a an accepted method [2,9,10,11,23]; however, the instrumentation needed to achieve sufficient stability following lumbar corpectomy is controversial. Biomechanical studies revealed that the highest achievable stability is provided by dorso-ventral instrumentation [11,15], but it remains unclear what degree of stiffness is needed to provide osseous healing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Defect-restoration with bone cement or a cage is a an accepted method [2,9,10,11,23]; however, the instrumentation needed to achieve sufficient stability following lumbar corpectomy is controversial. Biomechanical studies revealed that the highest achievable stability is provided by dorso-ventral instrumentation [11,15], but it remains unclear what degree of stiffness is needed to provide osseous healing.…”
Section: Discussionmentioning
confidence: 99%
“…The defect can be restored using bicortical bone graft or, in case of vertebral metastasis, with bone cement [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…A suitable technique was initially described for metastatic disease of the spine by Scoville et al (1967) and consists in wiring of laminae to occiput and acrylic plastic encasement of wires, occiput and spinous processes. The technique employed in the present series of patients is slightly altered.…”
Section: Discussionmentioning
confidence: 99%
“…In 1959, Knight [48] described five patients with cervical spondylosis, chronic fracture-dislocation, and atlantoaxial subluxation in rheumatoid arthritis whose cervical spine he fixed with acrylic cement. Scoville et al [73] in 1967 reported use of methylmethacrylate in patients with metastatic tumors of the cervical spine and spinal cord compression. They filled the anterior vertebral-body defects with methacrylate, without intending it as internal fixation.…”
Section: Cervical Fusion and The Development Of Current Instrumentationsmentioning
confidence: 99%